PENDEKATAN KOGNITIF UNTUK MENURUNKAN KECENDERUNGAN PERILAKU DELIQUENSI PADA REMAJA - Hartati, Sri (HUMANITAS (Jurnal Psikologi Indonesia), 2012)
AbstractThis study used cognitive approach to reduce adolescentsâ delinquency tendency. This approach aims to help adolescent be able to evaluate and criticize their negative self concept. Participants were 10 adolescents, aged between 13 to 15 years, who have a tendency of high and medium delinquency behavior. Five participants included in the experimental group and five participants in the control group. The Result of Wilcoxon SignedRanks Test showed there are decreasing in subjectâs delinquency behavior after cognitive therapy, that was while the pre-test to post-test with a value of z = -1.753 with p = .04 (p <0.05). While the post-test to follow-up, with the value z = - 0.944 with p = .173 (p> 0.05). While the pre-test to follow-up with the value z = - 0.677 with p = .249 (p> 0.05). The results showed that writing negative criticism about their self in the application of cognitive approachable to reduce delinquency behavior tendency inadolescents.Keywords: cognitive approach, delinquency behavior tendency.